Rice biotechnology : (Wiley, 2001)
Rice is the most important food crop for half the world's population. Over the last three decades, the imporvement in human nutrition and health in Asia has largely been attributable to a relatively stable and affordable rice supply. The challenge to produce enough rice for the future, however, remains daunting, as the current rate of population growth outpaces that of increases in rice production. Science has a central role to play in raising rice productivity and this book highlights areas of plant science that are particularly relevant to solving the major constraints on rice production. Examining molecular, genetic and cellular techniques, it considers recent advances in four research approaches for increasing yields and improving the nutritional quality of rice.